Commercial Law in the Middle East - Mallat, Chibly; Ruttley, Hilary Lewis (Middle East and Islamic Studies - Book Archive pre-2000., 1995)
Preface by The Right Honourable The Lord Woolf "[The editors] are to be congratulated on bringing together in a book this significant collection of papers which, together with their introductory overview, provide a 'multi-faceted insight into commercial law and practice in the Middle East'. For those, like myself, who have limited knowledge of the subject, this book will provide an admirable introduction. For those who are already well-informed, there will be found in this book insights as to the development of law and practice in the Middle East which complements their existing knowledge. This book provides an instructive and stimulating contribution to a subject, the importance of which is becoming increasingly appreciated. I congratulate the authors of the papers on their contributions and hope that this book will reach the wide audience it deserves."